2017
DOI: 10.1055/s-0042-122146
|View full text |Cite
|
Sign up to set email alerts
|

Wenn man sich selbst einfach nicht „riechen” kann

Abstract: Olfactory Reference Disorder is a little explored and widely unknown phenomenon, even research has shown more interest in it during the last years. This review summarizes the existing literature and illustrates its findings with a case history. The databases PubMed, PsychNet, PsychPub, Hogrefe EContent and the Cochrane Library (CENTRAL) were searched for keywords. The identified literature shows that there is a big lack of well-designed studies concerning ORS, in all areas of its nosology. The suffering of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
0
0
1
Order By: Relevance
“…Using the ICD-11 CDDR of ORD, we determined a prevalence of 5.5% in our sample. Our findings are consistent with the findings of Schmidt et al (2017) who suggested that ORD is relatively common in non-clinical settings. Indeed, according to our estimated prevalence of 5.5%, ORD might be more prevalent than other mental disorders in university / college students.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Using the ICD-11 CDDR of ORD, we determined a prevalence of 5.5% in our sample. Our findings are consistent with the findings of Schmidt et al (2017) who suggested that ORD is relatively common in non-clinical settings. Indeed, according to our estimated prevalence of 5.5%, ORD might be more prevalent than other mental disorders in university / college students.…”
Section: Discussionsupporting
confidence: 93%
“…This is the first study exploring the prevalence of ORD measured in accordance with the newly formalized ICD-11 required features, assessed in a non-clinical German university student sample. There are only a few previous studies, which, in the absence of standardized diagnostic categorization, captured the disorder, albeit with different criteria, that reported prevalence rates of 2.1% in a sample of Japanese university students (Kasahara & Kenji, 1971), 2.4% in a sample of Chinese university students (Zhou et al, 2018) and 6.4% in a sample representative of the German general population (Schmidt et al, 2017). Using the ICD-11 CDDR of ORD, we determined a prevalence of 5.5% in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personen mit ORS berichten bezüglich ihres Körper-geruches von Ekel und Abneigung [Schmidt et al, 2017]. Aus bisherigen Untersuchungen geht hervor, dass 95-100% der von ORS Betroffenen mindestens eine Sicherheitsverhaltensweise zeigen, um sich dieses Geruchs zu entledigen bzw.…”
Section: Ekelempfindlichkeit Und Orsunclassified